INTERPRETASI MASYARAKAT TENGGER TERHADAP PENGELOLAAN TAMAN NASIONAL BROMO TENGGER SEMERU DI KABUPATEN LUMAJANG - , DYAH TIMURYANTI; , Ir. Gunung Rafjiman, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
One effort to protect the diversity of flora and fauna is by determination of forest area that has certain characteristic as National Park in Indonesia. Such determination is regulated by Law No. 14/1999 on Forestry and Goverment Regulation No. 68/1998 on Conservation Forest. The determination of Bromo Tengger Semeru National Park is based on The Decree of Forestry Minister No. 178/Menhut-II/2005 and it had direct impact to Tengger Ranupane people that live and depend on the forest. This research intended to identity the interpretation and behavior of local people to forest management and to identity the efforts by the park management to realize forest conservation. Regulation which is applied in the national park management is to limit people,s activities to use non wood forest, particularly firewood, grass, and plant for custom ceremonies. However, people accept over the regulation because the management allowed them to use non wood forest product. In addition, forest management gave positive impact for their welfare. It was indicated by peopleâs involvement in some forest management activities particularly in ecotourism activities such as tourist guide service and tourist facility maintenance that can provide additional revenue for them. Positive interpretation of Tengger Ranupane people on Bromo Tengger Semeru National Park management encourage them to behave positively by keeping and maintenance forest resource without damaging it. Moreover, people voluntarily participate in forest conservation, observation, and rehabilitation. It was done to make conserved forest benefit for both present dan future generation.